The Effect of Profitability, Leverage, and Capital Intensity Against Tax Avoidance: (Study on Listed Manufacturing Companies) at ISSI in 2020-2024) - Alifia Azahara; Wahyu Iryana; Ainul Fitri (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to determine the effect of profitability, leverage, and capital intensity on tax avoidance in manufacturing companies registered with ISSI in 2020-2024. Tax avoidance is a company strategy to minimize the tax burden, which can impact company policy. The approach used is quantitative with a population of 72 companies. The sample selected through purposive sampling and obtained 26 companies with a total of 130 observations. This research is quantitative research and hypothesis testing in this study uses panel data regression with Eviews 13. Based on the appropriate model is the Fixed Effect Model (FEM). The results of the study indicate that profitability, leverage have a negative effect on tax avoidance and capital intensity has a positive effect on tax avoidance. Simultaneously, profitability, leverage, capital intensity affect tax avoidance.